2018
DOI: 10.1158/0008-5472.can-17-1688
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory NKR-P1B:Clr-b Recognition Axis Facilitates Detection of Oncogenic Transformation and Cancer Immunosurveillance

Abstract: Natural killer (NK) cells express receptors specific for MHC class I (MHC-I) molecules involved in "missing-self" recognition of cancer and virus-infected cells. Here we elucidate the role of MHC-I-independent NKR-P1B:Clr-b interactions in the detection of oncogenic transformation by NK cells. Ras oncogene overexpression was found to promote a real-time loss of Clr-b on mouse fibroblasts and leukemia cells, mediated in part via the Raf/MEK/ERK and PI3K pathways. Ras-driven Clr-b downregulation occurred at the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Santos-Juanes' newest study showed higher LLT1 expression was contributed to the risk of neck cutaneous squamous cell carcinoma (cSCC) nodal metastasis, which implicates LLT1 may also be a potential target to block cSCC nodal metastasis [57] . Similar results have also been seen in mice; inhibition of NKRP1B: Clr-b axis could enhance the NK cell-mediated immune surveillance to oncogenic transformation [52] . Due to the important role of LLT1 in tumor progression and metastasis, monoclonal antibody blocking of LLT1 to enhance NK cell cytotoxicity may provide a novel treatment to prevent tumor metastasis.…”
Section: Llt1 As An Immunotherapeutic Target For Breast Cancer and Prostate Cancersupporting
confidence: 79%
See 1 more Smart Citation
“…Santos-Juanes' newest study showed higher LLT1 expression was contributed to the risk of neck cutaneous squamous cell carcinoma (cSCC) nodal metastasis, which implicates LLT1 may also be a potential target to block cSCC nodal metastasis [57] . Similar results have also been seen in mice; inhibition of NKRP1B: Clr-b axis could enhance the NK cell-mediated immune surveillance to oncogenic transformation [52] . Due to the important role of LLT1 in tumor progression and metastasis, monoclonal antibody blocking of LLT1 to enhance NK cell cytotoxicity may provide a novel treatment to prevent tumor metastasis.…”
Section: Llt1 As An Immunotherapeutic Target For Breast Cancer and Prostate Cancersupporting
confidence: 79%
“…NKRP1A is encoded by KLRB1 and CD4 + T cells, invariant NKT cells, and γδ-T cells have also been shown to express NKRP1A [49] . In mice, CLEC2D encodes the protein Ocil/Clr-b, which interacts with NKR-P1B/D [52][53][54] .…”
Section: Llt1 and Nkrp1amentioning
confidence: 99%
“…However, a similar host-pathogen evolutionary interplay is revealed by the engagement of some of the m12 alleles through the activating NKR-P1A/C receptors that avert the MCMV decoy strategy 22 . The mouse Clr-b ligand is also a very sensitive marker of cell health that is rapidly downregulated during chemotherapy-induced genotoxic and cellular stress 23 or poxvirus infection 24 or oncogenesis25 . Concomitantly, recent studies showed that NKR-P1B:Clr-b missing-self recognition plays a key and non-redundant role in bone marrow transplantation 26,27 and cancer immunosurveillance25 in a mouse models.…”
Section: Introductionmentioning
confidence: 99%
“…The biotechnology company, TCR2, is exploring CD3ε-scFv fusions (Figure 10). Utilizing their TruC platform, the tumor specific binding scFv is fused to the extracellular domain of CD3ε, allowing for complex activation upon scFv-target binding, bypassing TCRα/β-MHC interactions [333]. Similarly, Triumvira has fused two scFvs in place of the MHC I binding head domain of CD8.…”
Section: Chimeric Antigen Receptor (Car)-t and Nk Cellsmentioning
confidence: 99%